2006
DOI: 10.1161/circulationaha.106.625061
|View full text |Cite
|
Sign up to set email alerts
|

Nitrative Inactivation of Thioredoxin-1 and Its Role in Postischemic Myocardial Apoptosis

Abstract: Background-Intracellular proteins involved in oxidative stress and apoptosis are nitrated in diseased tissues but not in normal tissues; definitive evidence to support a causative link between a specific protein that is nitratively modified with tissue injury in a specific disease is limited, however. The aims of the present study were to determine whether thioredoxin (Trx), a novel antioxidant and antiapoptotic molecule, is susceptible to nitrative inactivation and to establish a causative link between Trx ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 50 publications
3
80
0
Order By: Relevance
“…In a recent study, we have demonstrated that besides three previously reported posttranslational Trx modifications which all occur at the cysteine residue, Trx can also be modified at the tyrosine residue (protein nitration) in a peroxynitrite-dependent fashion [28]. More interestingly, in contrast to the reversible (by Trx reductase) oxidative Trx inactivation, nitrative modification of Trx results in an irreversible inactivation [28].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In a recent study, we have demonstrated that besides three previously reported posttranslational Trx modifications which all occur at the cysteine residue, Trx can also be modified at the tyrosine residue (protein nitration) in a peroxynitrite-dependent fashion [28]. More interestingly, in contrast to the reversible (by Trx reductase) oxidative Trx inactivation, nitrative modification of Trx results in an irreversible inactivation [28].…”
Section: Discussionmentioning
confidence: 87%
“…More interestingly, in contrast to the reversible (by Trx reductase) oxidative Trx inactivation, nitrative modification of Trx results in an irreversible inactivation [28]. Therefore, nitric oxide and its secondary reaction products, particularly peroxynitrite, exert opposite effect on Trx activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Trx is able to interact with transcription factors and to undergo the posttranslational modifications such as: oxidation of the thiol groups of Cys-32 and -35, glutathionylation at Cys-73 (Casagrande et al 2002), Snitrosylation at Cys-69 or Cys-73 (Haendeler et al 2002), nitrative modification at Tyr-49 (Tao et al 2006) and also glycation (Yuan et al 2010). This capability is also consistent with the role of Trx system in angiogenesis signaling.…”
Section: Thioredoxin Systemmentioning
confidence: 99%
“…Additionally, NO can possibly mediate cell death or injury via S-nitrosylation or nitration reactions on other TRX-like proteins, such as TRX itself and glutaredoxin [71,157,158]. In addition to PDI, S-nitrosylation is likely to affect critical thiol groups on other chaperones, such as HSP90 in the cytoplasm [159] and possibly GRP in the ER.…”
Section: The Unfolded Protein Response (Upr) and Pdimentioning
confidence: 99%